Phylogenetic relationships of Tectoribates: nymphal characters of new North American species place the genus in Tegoribatidae (Acari, Oribatida) - Behan-Pelletier, Valerie M.; Walter, David E. (Zootaxa, 2013)
Species in the oribatid mite genus Tectoribates are primarily Palaearctic and Neotropical, with scattered, unidentified records from North America. Herein, we describe 3 new Tectoribates species from dry forest and prairie habitats in North America: T. alcecampestris sp. nov., from Alberta, T. borealis sp. nov., from southern Alberta and Ontario, both on the basis of adults and nymphs, and T. campestris sp. nov., from dry grassland habitats in Ontario and Kansas, on the basis of adults. We provide a revised and expanded diagnosis for adults of Tectoribates. We assess relationships of Tectoribates, using characters of adults and newly discovered apheredermous, plicate immatures. We include observations on Pseudotectoribates which is closely related to Tectoribates. The closest relatives of these genera are hypothesised to be among the Tegoribatidae (Achipterioidea) rather than among the Achipteriidae (Achipterioidea), Oribatellidae (Oribatelloidea), or Ceratozetoidea, as suggested in previous classifications. Finally, we give a key to adults of the world fauna of Tectoribates.